Association of Blood Pressure Trajectory With Mortality, Incident Cardiovascular Disease, and Heart Failure in the Cardiovascular Health Study. - Smitson, Christopher C; Scherzer, Rebecca; Shlipak, Michael G; Psaty, Bruce M; Newman, Anne B; Sarnak, Mark J; Odden, Michelle C; Peralta, Carmen A (Am J Hypertens, 2017)
BACKGROUND: Common blood pressure (BP) trajectories are not well established in elderly persons, and their association with clinical outcomes is uncertain. METHODS: We used hierarchical cluster analysis to identify discrete BP trajectories among 4,067 participants in the Cardiovascular Health Study using repeated BP measures from years 0 to 7. We then evaluated associations of each BP trajectory cluster with all-cause mortality, incident cardiovascular disease (CVD, defined as stroke or myocardial infarction) (N = 2,837), and incident congestive heart failure (HF) (N = 3,633) using Cox proportional hazard models. RESULTS: Median age was 77 years at year 7. Over a median 9.3 years of follow-up, there were 2,475 deaths, 659 CVD events, and 1,049 HF events. The cluster analysis identified 3 distinct trajectory groups. Participants in cluster 1 (N = 1,838) had increases in both systolic (SBP) and diastolic (DBP) BPs, whereas persons in cluster 2 (N = 1,109) had little change in SBP but declines in DBP. Persons in cluster 3 (N = 1,120) experienced declines in both SBP and DBP. After multivariable adjustment, clusters 2 and 3 were associated with increased mortality risk relative to cluster 1 (hazard ratio = 1.21, 95% confidence interval: 1.06-1.37 and hazard ratio = 1.20, 95% confidence interval: 1.05-1.36, respectively). Compared to cluster 1, cluster 3 had higher rates of incident CVD but associations were not statistically significant in demographic-adjusted models (hazard ratio = 1.16, 95% confidence interval: 0.96-1.39). Findings were similar when stratified by use of antihypertensive therapy. CONCLUSIONS: Among community-dwelling elders, distinct BP trajectories were identified by integrating both SBP and DBP. These clusters were found to have differential associations with outcomes.